Study on the disease burden of exposure to microbial aerosols in municipal wastewater treatment plants - GAO Tingting; CAI Chuanzun; CHEN Nuo (Xi'an Gongcheng Daxue xuebao)
Municipal wastewater treatment plant workers, who are exposed to the microbial aerosol generated during the operation environment, can inhale pathogenic microorganisms through breathing, which ultimately causes loss of healthy life span. In response to this problem, this study quantitatively identifies aerosol particles and the pathogens they carry in the air of wastewater treatment plants. It also clarifies the occupational exposure risks faced by workers. By combining quantitative risk assessment of microorganisms with disease burden research methods, the study employs the disability adjusted life year (DALY) as a key health evaluation index. A new model and calculation method system for microbial aerosol occupational health risk assessment based on DALY were proposed, and further selection of typical pathogens for disease burden calculation was conducted. The results show that during the occupational exposure process of typical wastewater treatment plant workers, the health losses caused by inhaling norovirus, adenovirus, and rotavirus through aerosols are significantly higher compared with WHO standards, and process improvement or restriction of exposure is needed.